2019
DOI: 10.1126/scitranslmed.aau0164
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological enhancement of KCC2 gene expression exerts therapeutic effects on human Rett syndrome neurons and Mecp2 mutant mice

Abstract: Rett syndrome (RTT) is a neurodevelopmental disorder caused by mutations in the methyl CpG binding protein 2 (MECP2) gene. There are currently no approved treatments for RTT. The expression of K+/Cl− cotransporter 2 (KCC2), a neuron-specific protein, has been found to be reduced in human RTT neurons and in RTT mouse models, suggesting that KCC2 might play a role in the pathophysiology of RTT. To develop neuron-based high-throughput screening (HTS) assays to identify chemical compounds that enhance the expressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
107
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(115 citation statements)
references
References 97 publications
8
107
0
Order By: Relevance
“…Similarly, Nifedipine abolished the reduction driven by CX546 on the expression of Rest, a gene that is generally upregulated in null samples (Abuhatzira et al, 2007). In good accordance with the functional data, in panel J we found that only CX546 increased the ratio of the expression levels of Kcc2 and Nkcc1, therefore indicating a faster rate of maturation of GABA signaling (Tang et al, 2019;Hinz et al, 2019).…”
Section: The Enhancement Of Glutamatergic Transmission Within An Earlsupporting
confidence: 85%
See 1 more Smart Citation
“…Similarly, Nifedipine abolished the reduction driven by CX546 on the expression of Rest, a gene that is generally upregulated in null samples (Abuhatzira et al, 2007). In good accordance with the functional data, in panel J we found that only CX546 increased the ratio of the expression levels of Kcc2 and Nkcc1, therefore indicating a faster rate of maturation of GABA signaling (Tang et al, 2019;Hinz et al, 2019).…”
Section: The Enhancement Of Glutamatergic Transmission Within An Earlsupporting
confidence: 85%
“…From a functional perspective, CX546 rescued the responsiveness of null neuronal networks to stimuli, while decreasing their intracellular Cllevels, which suggests a restored responsiveness to GABA. This result fits with the recovered transcriptional levels of Kcc2, the neuron specific K + -Cl − co-transporter (KCC2) that is crucial for GABA signaling maturation (Ben-Ari et al, 2012) and its normalization in Rett syndrome currently represents a promising therapeutic approach (Tang et al, 2016;Tang et al, 2019;Lozovaya et al, 2019). Importantly, the simultaneous treatment of Mecp2 null neurons with CX546 and Nifedipine, a voltage gated calcium channels blocker, restricted the observed transcriptional rescues, therefore proving that most of the beneficial effects were due to enhanced neuronal activity.…”
Section: Discussionsupporting
confidence: 65%
“…In an elegant and very recently published study, small molecules were selected to enhance expression of Kcc2/KCC2 for effective rescue of a modeled Rett Syndrome phenotype (Tang et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Deficits in Kcc2 activity are also believed to contribute to the development of temporal lobe epilepsy (17,18), in addition to other traumas including ischemia and neuropathic pain (19,20). Given the critical role that Kcc2 plays in determining the maturation of inhibitory neurotransmission, subtle changes in its function are also strongly implicated in autism spectrum disorders (ASD) (21), Down syndrome (22), fragile X syndrome (23), and Rett syndrome (24)(25)(26).…”
Section: Introductionmentioning
confidence: 99%